Shifting Agendas: Private Consultants and Public Planning Policy. Issue 6 (November 2019) - Linovski, Orly
Despite concerns about the privatization of urban planning practices, there is little known about the professional actors involved in this restructuring. Private-sector consultants, though beholden to the same professional standards as public-sector employees, face competing pressures of an entrepreneurial fee-for-service business model. This article examines the role of planning consultants in shaping public policy agendas, by analyzing the redevelopment of Downsview Park in Toronto, Ontario. Drawing from interview and archival data, I find that private-sector planning consultants had influence in prioritizing policy agendas by propagating the need for sped-up processes and allowing landowners to "pay for priority." The fluidity of professionals between firms, sectors, and projects reinforced the perceived value and neutrality of consultant expertise. These strategies worked to erode the differences between public- and private-sector planning processes, resulting in a high degree of influence for development interests.